PENCABUTAN IZIN TAMBANG OLEH BKPM: TELAAH PROSES PENCABUTAN DAN KEWENANGANNYA - Khansa Nur Aidah (CV Rewang Rencang, 2024)
This paper discusses the management of natural resources in Indonesia, particularly focusing on the revocation of Mining Business Licenses (IUP) by the Badan Koordinasi Penanaman Modal (BKPM). Referring to Article 33 paragraph (3) of the 1945 Constitution, the state controls mineral and coal resources for the welfare of the people. With the enactment of the Mineral and Coal Law and related policies, the authority to revoke IUP has shifted from local to central government. This study analyzes the legal basis, process, and implications of IUP revocation by BKPM, as well as the legal challenges arising from this delegation of authority, highlighting the importance of sustainable and transparent regulations in natural resource management.